ETHICAL CONSIDERATIONS ON THE USE OR THE ABUSE OF CT-SCAN INVESTIGATIONS - REBELEANU, Codrin; ALUAȘ, Maria (Studia Universitatis Babeş-Bolyai Bioethica, 2016)
The imagistic investigations such as classical radiology, Computed Tomography (CT) examinations, nuclear magnetic resonance (NMR) are essential investigations for carrying out a diagnosis of accuracy, being indispensable to the practice of a quality medical act. The CT type of investigation represented, one decade ago, a practice of the high medicine, becoming in present one of the usual techniques of investigation being often preferred instead of classical radiology. The advantages of this type of investigation are however expensive and also expose the patient to a high degree of irradiation. As it is not a routine investigation, it is not justified in all situations. The negative consequences of carrying out unnecessary investigations are reflected on the one hand on the sanitary system by the additional costs involved, and on the other hand on the patient, who is irradiated, with no existence of a real benefit for their health. In this article, the authors attempt: 1) to evaluate the dimension of the problematic excess of CT investigations on the basis of the analysis of a case, 2) to identify the main causes which lead to this excess, 3) pointing also possible negative consequences of the exaggerated use of these practices. Considerații etice cu privire la uzul sau abuzul investigațiilor de tip CT. Investigațiile imagistice de tipul radiologiei clasice, examinările de tip Computer Tomograf (CT), rezonanță magnetică nucleară (RMN) sunt investigații esențiale pentru realizarea unui diagnostic de acuratețe, fiind indispensabile practicării unui act medical de calitate. Investigarea de tip CT reprezenta, în urmă cu numai un deceniu, o practică a medicinii de vârf, devenind în prezent una dintre tehnicile de investigație uzuale, fiind adesea preferată în locul radiologiei clasice. Avantajele pe care le prezintă acest tip de investigație sunt însă costisitoare și totodată expun pacientul la un grad ridicat de iradiere. Nefiind o investigație de rutină, nu este justificată în toate situațiile. Urmările negative ale realizarii unor investigații inutile se reflectă pe de o parte asupra sistemului sanitar, prin costurile suplimentare antrenate, și pe de altă parte asupra pacientului, care este iradiat, fără a exista un beneficiu real pentru sănătatea sa. În acest articol, autorii încearcă: 1) să evalueze dimensiunea problematicii excesului de investigație CT, plecând de la analiza unui caz, 2) să identifice principalele cauze care duc la acest exces, 3) indicând totodată și posibile consecințe negative ale uzului exagerat al acestor practici. Cuvinte-cheie: CT- scan, abuz de investigații, iradiere medicala, consimțământ informat, educația pacienților